Evaluation of the effect of selected complementary and alternative medicines on the efficacy of cancer chemotherapeutic agents - Green, Blake Delroy (My University, 2022)
Breast cancer is the most diagnosed cancer worldwide, and the second leading cause of cancer-related deaths. In Sub-Saharan Africa breast cancer incidence is associated with younger women, late-stage diagnosis, poor prognosis, and limited availability of chemotherapy. Despite the favourable prognosis of certain subtypes of breast cancers, treatment failure occurs as result of drug resistance. Drug resistance is facilitated by the P-glycoprotein (PgP) transporter protein which functions as an efflux pump and is overexpressed in many types of cancer. The upregulation of the inducible protein, haem oxygenase-1 (HMOX1), has been identified as an additional role player in cancer drug resistance. Complementary and alternative medicines (CAMs) are frequently used by cancer patients to improve treatment outcomes and alleviate drug adverse effects. There is a lack of information regarding the effect CAMs may have on the effectiveness of cancer drugs. This study investigates the potential interactions of selected CAMs with chemotherapy drugs using MCF-7 breast cancer cell line as a model. The MCF-7 breast cancer cells were maintained in culture and the cytotoxic efficacy of the chemotherapy drugs and CAMs were determined by the MTT cell viability assay. Fluorescent stains were used to evaluate morphological changes. The effects of active compounds on the PgP function were determined by the calcein-AM retention assay. Immunofluorescence microscopy was used to evaluate protein expression levels of PgP and of HMOX1 in the MCF-7 cell line Doxorubicin was most active chemotherapy drug in MCF-7 cells and was selected as the positive control in this study. Of the selected CAMs evaluated, resveratrol, synephrine and caffeine were the most active in MCF-7 cells with IC50 values of 80.54 µM, 149.30 µM and 167.40 µM, respectively over 48 hours. In combination treatments of doxorubicin with the active CAMs at IC50 concentrations, resveratrol significantly reduced the potency of doxorubicin after 24 hours whilst synephrine enhanced the potency of doxorubicin after 48 hours. Morphological evaluation showed cellular changes consistent with apoptosis when cells were treated with doxorubicin and resveratrol whilst some cells showed necrosis when exposed to the CAMs. PgP efflux activity was stimulated at low concentrations of doxorubicin and resveratrol whilst high concentrations of synephrine and caffeine were required after a 24 hour treatment period. During combinations studies, resveratrol enhanced PgP efflux activity in the presence of 0.05 µM and 0.5 µM concentrations of doxorubicin. In contrast, synephrine and caffeine inhibited the PgP efflux activity when used in combination with doxorubicin. Immunofluorescence showed that doxorubicin strongly induced the expression of PgP protein after both 24 hours and 48 hours. The CAMs had no effects on baseline PgP expression during single-agent treatment. When combined with doxorubicin, resveratrol and caffeine suppressed the doxorubicin increased PgP expression levels after 48 hours. The expression levels of the HMOX1 were induced by doxorubicin and synephrine following single agent treatment. In combination treatments, all the active CAMs suppressed the doxorubicin induced increase in expression of HMOX1. In summary, synephrine increased the efficacy of doxorubicin. Synephrine and caffeine inhibited doxorubicin associated PgP efflux activity. Resveratrol and caffeine were effective in suppressing the doxorubicin induced increase in expression of PgP. All the CAMs suppressed the doxorubicin induced HMOX1 expression in MCF-7 cells. The data indicate the CAMs investigated in this study may affect the clinical efficacy of doxorubicin. Further investigation is required to elucidate the CAM effects on the efficacy of chemotherapeutic drugs.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022